2019
DOI: 10.1055/s-0039-1694071
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Tobacco Use: Ill Effects on Reproductive, Maternal, Newborn, Child Health, and Adolescent (RMNCHA) Program—A Review

Abstract: Most people are aware that tobacco causes cancer, heart disease, chronic obstructive pulmonary disease, and major health problems, leading to high morbidity and mortality; however, many are not aware of its ill effects on the reproductive health of men and women as well as their children. This article has summarized the current research evidence from literature search to date, including prevalence of tobacco use, types of tobacco use, its effects on male and female fertility, pregnancy and their progeny in ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…Cessation of smoking depends on many factors that can be personal and social. Many smokers make several attempts to quit smoking but fail to stay abstinent [10]. The early age initiation of smoking is majorly the cause for addiction effects.…”
Section: Methodsmentioning
confidence: 99%
“…Cessation of smoking depends on many factors that can be personal and social. Many smokers make several attempts to quit smoking but fail to stay abstinent [10]. The early age initiation of smoking is majorly the cause for addiction effects.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work has suggested that tobacco use is less likely to change during pregnancy compared with other substances. 47 It is important to consider given its potential influence on low birth weight, preterm birth, and congenital anomalies 48 and that tobacco may interact with other substances to increase risk for adverse neonatal outcomes. 49 Future research may explore specific service offerings, patterns of engagement, and their impact on neonatal outcomes.…”
Section: Researchmentioning
confidence: 99%
“…The Australian Category D definition is “drugs which have caused, are suspected to have caused or may be expected to cause, an increased incidence of human foetal malformations or irreversible damage” [ 41 ]. The immediate adverse foetal and neonatal outcomes (i.e., pre-term birth, lower birthweight, stillbirth, SIDS) tend to overshadow and draw attention away from the adverse impact of in-utero nicotine exposure on foetal programming and the consequences to the offspring of lifelong increased risks for acute and chronic illness and disease including childhood obesity, early onset cardiovascular and respiratory disease and cognitive and behavioural barriers (attention-deficit/hyperactivity disorder (ADHD) and learning challenges) [ 42 46 ].…”
Section: Introductionmentioning
confidence: 99%